2010 International Conference on Simulation of Semiconductor Processes and Devices 2010
DOI: 10.1109/sispad.2010.5604573
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulation of focused ion beam processing using the level set method

Abstract: Abstract-Three-dimensional simulations of focused ion beam milling, which use the level set method for surface evolution, are presented for the first time. This approach allows the inherent description of topological changes. The surface rates are calculated using Monte Carlo ray tracing in order to incorporate shadowing as well as redeposition. Parallelization is used to reduce the computation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It was observed that for all doses below 10 16 ions/cm 2 , surface swelling occurred. The surface swelling is believed to occur in order to relieve strain caused by implanted Ga ions [8] as well as sub surface damage [20]. By increasing the current at corresponding doses a reduction in surface swelling, which could be the indicative of greater removal of substrate material, was also observed (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…It was observed that for all doses below 10 16 ions/cm 2 , surface swelling occurred. The surface swelling is believed to occur in order to relieve strain caused by implanted Ga ions [8] as well as sub surface damage [20]. By increasing the current at corresponding doses a reduction in surface swelling, which could be the indicative of greater removal of substrate material, was also observed (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Since a focused ion beam diameter is commensurable to the projected ion range, its ERF must be calculated in two-dimensional geometry. To describe ion flux density along the radius of CFIB the way from [12] is used:…”
Section: Mathematical Formulation Of Energy Release Functionmentioning
confidence: 99%